Walled States, Waning Sovereignty - Brown, Wendy (Book collections on Project MUSE., 2017)
Discusses the spate of wall-building by countries around the world and considers the reasons why walls are being built in an increasingly globalized world in which threats to security come from sources that cannot be contained by brick and barbed wire.